Implementasi Kebijakan Kurikulum 2013 di SMK Al Washliyah 13 Kota Tebing Tinggi - Muhammad Iqbal; Kiranti Silvia; Lutfiah Azhar Nst; Umi Masnah; Wahyu Ardian Nst (Departement of Mathematics Education, 2023)
The 2013 curriculum policy is one of the policies in the field of education launched by the government where the government adds an attitude assessment to the curriculum structure in the 2013 curriculum policy. The existence of this assessment then forms the basis that the 2013 curriculum is a character-based curriculum. This study aims to determine the implementation of the 2013 curriculum policy at SMK Al Washliyah 13 Tebing Tinggi City. This study uses a descriptive research method with a qualitative approach. The implementation of the 2013 curriculum policy at Al Washliyah 13 Vocational High School, Tebing Tinggi City, has been running effectively in the good category. Teachers have been able to carry out teaching and learning activities and the assessment process well. Teachers are able to implement teacher and student books in learning activities. The school has governance that is categorized as good to support the implementation of the 2013 curriculum. The school principal also manages the curriculum quite well and tries to provide the facilities and amenities needed by the 2013 curriculum.